STUDIES ON THE ROUTE OF SYNTHESIS OF THE THYROID HORMONE - Fawcett, David M. (My University, 1952)
Certain aspects of the biochemistry of the thyroid gland have been studied. The techniques of filter paper chromatography and radioautography were used to separate and identify the iodine-containing amino acids of the gland, and were modified somewhat, in order to obtain reliable results. Although a series of preliminary experiments were performed with the thyroid glands of rats in vivo, the main part of this work made use of the in vitro technique. Surviving tissue slices were incubated in the presence of the radioactive tracer, iodine131. Evidence was obtained which indicated that at least two of the amino acids found "free" in the thyroid gland were degraded by the gland to inorganic iodide. The mechanism of action of a number of thyroid gland inhibitors was investigated. It was found that all but two of the materials studied led to the formation in the tissue slices of unidentified iodine—containing materials with the simultaneous disappearance of inorganic iodide. Hence, at least a part of the goitrogenic nature of these inhibitors would appear to be due to the "removal" of iodide. It was found chat one portion of the inhibition caused by 3 - fluorotyrosine could be "reversed" in vitro with tyrosine, interesting sex variations in thyroid gland activity were observed during these experiments.
Keywords: Thyroid gland